Road Traffic Accidents and Environmental Risk Factors in Erbil City - Hayman Mohammed saeed; Kameran Hassan Ismail (Polytechnic Journal)
Motorization has improved the lives of people and societies; these benefits have to go with a value. Though the number of lives lost in road accidents in high-income nations points to a downward style in recent decades, for many of the world's population, the liability of road-traffic injury in terms of social and economic costs is rising considerably. This study aims to determine the prevalence of the environmental factors associated with the outcomes in Erbil city. A community-based cross-sectional descriptive household visits survey study was carried out from March-November 2021 and was composed of 3743 individuals selected through a multi‐stage sampling technique. A specially designed questionnaire was used to collect sociodemographic and environmental data from the participants through face-to-face interviews with the amount RTAs occurrence, Chi-square, and percent used with P-value ≤5 for significance. A total of 3743 road accidents were surveyed, and 675(18%) reported road accidents. Young males were main (53%), mean of age (28.5±18.26) years old. statistically, the highest prevalence occurred in urban location 550(81.5%), by drivers 475(70.4%) at daylight 410(60.7%), during rush hours. A significant association was reported between death proportion and the rural crash, on 80 km street speed, wet weather, rollover type, at night-shift, on Sunday, in January. The outcome of the present study shows a significant relationship between environmental situations and road traffic accidents in Erbil.